Use of English in the Scientific Community in France: Obstacles and Stakes - Chaplier, Claire (Baltic Journal of English Language, Literature and Culture, 2022)
English as a lingua franca (ELF) has emerged as a way of referring to communication in English between speakers with different first languages. That is the reason why ELF is the language used in science. Yet language is not limited to communication; it is also tied to the creation of concepts. As English is developed and transformed by its non-native users into an international scientific communication language, there is a risk of developing an impoverished form of English. The use of English as a lingua franca, devoid of culture, and used in scientific discourse may affect the transmission and the production of scientific knowledge. We can wonder about the consequences of the development of English in the scientific academic community and scientific teaching and learning contexts as all French university curricula have integrated English. Thus, this paper examines the different representations of science and the English language used in science. In conclusion, we propose the development of research in English for science, teacher training, teaching English for science and science in English (Content and Language Integrated Learning; henceforth CLIL) to students in the language teaching sector for non-linguists (LANSAD in French).